Identification of Key Factors in the Implementation of Geographic Information Systems for Public Administration - Br. Ketaren, Erpina; Ritonga, Syafruddin; Junita, Audi (Borong Newinera Publisher, 2025)
This study aims to identify key factors in the implementation of Geographic Information System (GIS) in public administration in Sibolangit Sub-district Office, Deli Serdang Regency. GIS plays an important role in improving efficiency, transparency, and accuracy in the management of geographic data. The method used in this study is a qualitative approach with data collection techniques through interviews, observations, and document analysis. The results show that GIS has improved time efficiency and data accuracy in public administration, but its effectiveness is still affected by several factors. The main obstacles found include unstable technological infrastructure, limited technical training for staff, and lack of policies that support the use of GIS in a structured manner. Technical, organizational, and human resource factors are the keys to the successful implementation of GIS. This study concludes that to maximize the effectiveness of GIS, it is necessary to make improvements to technological infrastructure, increase human resource capacity, and develop policies that support the implementation of GIS in public administration.